The Effect of Schoology on the Students’ Writing Interest - Agustin Apriliani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThis research aimed to determine the effect of using Schoology as learning media on students’ writing interest. The research was done in a 2x2 experimental design with experimental and control classes selected as participants using purposive random sampling. The two groups had the same writing ability but received different learning media treatments, Picture Series for the control class, and Schoology for the experimental class. The Tukey’s test results showed that qobtain between columns A1 and A2(3.46) was higher than qtable (2.92) proving that using Schoology in teaching writing was significantly different from Picture Series. On the other hand, qobtain between cells A1B1and A2B1(4.47) was higher than qtable (3.08) proving that using Schoology differed significantly from Picture Series in teaching writing for students who had high interest. Then qobtain between cells A1B2and A2B2(0.41) was lower than qtable (3.08) proving that using Schoology did not differ significantly from Picture Series in teaching writing for students who had low interest. This study concludes that learning writing skills using Schoology affects students' levels of learning interests. Schoology, therefore, could be an alternative learning media platform for teaching and learning writing skills.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran Schoology terhadap minat menulis siswa. Penelitian dilakukan dalam rancangan eksperimen 2x2 dengan kelas eksperimen dan kelas kontrol dipilih sebagai partisipan dengan menggunakan purposive random sampling. Kedua kelompok memiliki kemampuan menulis yang sama tetapi mendapat perlakuan media pembelajaran yang berbeda yaitu Picture Series untuk kelas kontrol dan Schoology untuk kelas eksperimen. Hasil uji Tukey menunjukkan bahwa qobtain antara kolom A1 dan A2 (3,46) lebih tinggi dari qtabel (2,92) yang membuktikan bahwa penggunaan Schoology dalam pengajaran menulis berbeda secara signifikan dengan Picture Series. Di sisi lain, qobtain antara sel A1B1 dan A2B1 (4,47) lebih tinggi dari qtabel (3,08) membuktikan bahwa penggunaan Schoology berbeda secara signifikan dengan Picture Series dalam pengajaran menulis untuk siswa yang memiliki minat tinggi. Kemudian qobtain antara sel A1B2 dan A2B2 (0.41) lebih rendah dari qtabel (3.08) membuktikan bahwa penggunaan Schoology tidak berbeda secara signifikan dengan Picture Series dalam pembelajaran menulis untuk siswa yang memiliki minat rendah. Penelitian ini menyimpulkan bahwa pembelajaran keterampilan menulis menggunakan Schoology berpengaruh terhadap tingkat minat belajar siswa. Oleh karena itu, Schoology dapat menjadi platform media pembelajaran alternatif untuk pembelajaran keterampilan menulis.